Policy Implementation of the No Advance House Program at PTPilar Ksatria Tidar Nusantara - Sertunurisman, Muchamad; Rivai Zainal, Veithzal; Hakim, Azis (International Journal of Advanced Multidisciplinary, 2023)
Implementation of the Policy through the housing program without down payment, the company hopes to be able to catch up with the increasing demand for housing. Based on this, the authors can formulate this research problem, namely: How is the policy implementation of the house program without down payment at PT. Pilar Ksatria Tidar Nusantara Knights and what factors led to the implementation of the zero down payment housing program policy at PT. Pilar Ksatria Tidar Nusantara. In research on the implementation of subsidized housing, it was analyzed using the theory of Donald Van Meter and Van Horn (Suharsono, 2005:99) with six variables that affect implementation performance, namely: 1) Policy standards and targets, 2) Resources, 3) Inter-organizational communication and reinforcement activities, 4) Characteristics of implementing agents, 5) Economic, social and political environment 6) Attitudes of executors. The research approach that the authors use is descriptive qualitative, using key informants. Based on the results of the study that: 1) the implementation of the no-down payment housing program policy at PT. The Ksatria Tidar Nusantara pillar is good, as evidenced by the statements of both users and non-users who say this program is good and very useful for the community and 2) External constraints, namely the implementers involved in implementing the subsidized KPR program also experience various obstacles that External constraints do not only occur in policy implementers but also in society as the target group. These constraints include administrative problems such as KTPs that are not recorded at Disdukcapil, NPWP which has problems with entrepreneurs whose businesses have not been taxed while the conditions are that they must have an NPWP, as well as domiciles that do not match their original place of residence. Furthermore, the constraints on complaints from the public are related to communication which they feel has not reached them and other community acknowledgments such as some who feel that the entry fee is still too high even though it has been subsidized by the government.